2020
DOI: 10.1016/j.cell.2020.03.052
|View full text |Cite
|
Sign up to set email alerts
|

Heterochromatin-Driven Nuclear Softening Protects the Genome against Mechanical Stress-Induced Damage

Abstract: Highlights d Stretch triggers amplitude-dependent supracellular and nuclear mechanoresponses d H3K9me3 heterochromatin mediates nuclear stiffness and membrane tension d Nuclear deformation-triggered Ca 2+ alters chromatin rheology to prevent DNA damage d Supracellular alignment redistributes stress to restore chromatin state

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

30
433
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 427 publications
(466 citation statements)
references
References 86 publications
30
433
3
Order By: Relevance
“…It is possible that, in ATR-defective cells, deregulated topological and condensation activities may cause nuclear membranes invaginations and ruptures, nuclear fragmentation, and micronuclei formation; the heterochromatic and heavily condensed chromatin could instead result from the deregulation of the NRD complex 46 . Recent observations 47 showed that H3K9 trimethylation marked heterochromatin levels rearrange in response to mechanical stress at the NE and the recovery of the nucleus. In this scenario, our finding that a longterm depletion of ATR accumulates hypercompacted chromatin at the nuclear periphery and elevated levels of H3K9 trimethylation may therefore reflect the inability of ATR-depleted cells to properly recover from nuclear stress.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that, in ATR-defective cells, deregulated topological and condensation activities may cause nuclear membranes invaginations and ruptures, nuclear fragmentation, and micronuclei formation; the heterochromatic and heavily condensed chromatin could instead result from the deregulation of the NRD complex 46 . Recent observations 47 showed that H3K9 trimethylation marked heterochromatin levels rearrange in response to mechanical stress at the NE and the recovery of the nucleus. In this scenario, our finding that a longterm depletion of ATR accumulates hypercompacted chromatin at the nuclear periphery and elevated levels of H3K9 trimethylation may therefore reflect the inability of ATR-depleted cells to properly recover from nuclear stress.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is less obvious what mechanism would affect the transcription of nearby genes in the absence of an intermediate effect on genome organisation. Increased levels of DNA damage may be a contributing factor (Nava et al, 2020). Indeed, we have previously shown that γH2AX levels are increased in bone marrow cells from Suv39DKO chimeric mice.…”
Section: Discussionmentioning
confidence: 91%
“…Our findings here using our unique model of heterochromatin loss in primary immune cells complement several recent papers in different models and systems. In particular, a recent study used mechanical stress to disrupt heterochromatin stability in skin epidermis stem/progenitor cells (Nava et al, 2020). They also found a predominant down-regulation of gene expression, reduced lamina-association of heterochromatin domains, but were unable to find a correlation between H3K9me3-regulated regions and gene transcriptional changes (Nava et al, 2020).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…in response to deformation [154]. As the models used to interpret data were all based on assumptions on the contributions of the various components of the cell, the cell properties varied substantially between the studies, suggesting differences in how the results of different methods were obtained or analyzed [155].…”
Section: Powerful Tools For Assessing Cell Mechanicanical Properties mentioning
confidence: 99%